EVALUASI KEMAMPUAN LAHAN PADA LAHAN PERTANIAN DI KABUPATEN TAKALAR: Analysis of Land Capability Farmland in Takalar Regency - Tegar Ilham; Rismaneswati; Muhammad Nathan (Jurnal Ecosolum, 2021)
The dry land and paddy fields in Takalar Regency are quite extensive which have the potential to support efforts to maintain food security. Land potential can be estimated based on the land capability class. This study aims to determine the potential of dry land and paddy fields in Takalar Regency by using the land capability evaluation method. This research was conducted in Takalar Regency using a descriptive survey method. The field survey used the free survey method on several land units in paddy fields and dry land. Socio-economic data were collected by conducting interviews with farmers in each unit of land analysis. Mapping of land capability classes using Arc-GIS 10.3 software. The study used a simple, qualitative bounding approach developed by USDA (1975) with the criteria for land capability by Arsyad (2010). This study shows that on dry land there are several land capability classes with their respective sub-classes, namely IIIes, IIItews, IVt, IVw, VIt, and VIIt. In paddy fields, there are land grade classes IIIes, IIIews and IVw. Based on the results of the research, it can be concluded that on dry land there is a land capability class, there is a land capability class III , class IV, class VI, and class VI with the dominant limiting factors, namely slopes, erosion, and waterlogging (drainage and flood threat). Meanwhile, the paddy fields consist of class III, and class IV with the dominant limiting factors, namely erosion, drainage, and soil depth.